Clinical Predictors of Response to Magnetic Seizure Therapy in Depression: A Preliminary Report. Issue 1 (March 2019) - Kayser, Sarah; Bewernick, Bettina H.; Wagner, Stefanie; Schlaepfer, Thomas E.
Abstract : Objectives: Magnetic seizure therapy (MST) is a novel convulsive brain stimulation method in clinical testing, which is used as an alternative for electroconvulsive therapy in patients with treatment-resistant depression (TRD). Preliminary studies have suggested that MST leads to fewer cognitive adverse effects than electroconvulsive therapy but has similar efficacy. However, the clinical predictors of response to MST have not been evaluated yet. This study aimed to investigate whether these predictors can be identified in patients with TRD. Methods: Thirty-eight patients with TRD were included. As clinical predictors for treatment response, we used the diagnosis, sex, age, family history, and severity of depression, as well as the melancholic, psychotic, anxiety, and atypical depression symptoms. A response was defined as an improvement higher than 50% on the 28-item Hamilton Rating Scale for Depression. The binary logistic regression, stepwise linear regression, and effect sizes were calculated. Results: We found that 68.4% of the patients responded to MST. The responders had significantly fewer previous depressive episodes, less severe depression, and fewer melancholic (anhedonia) and anxiety symptoms than the nonresponders. In addition, responders were more likely to have a positive family history of depression than nonresponders. In particular, the number of previous episodes and a family history of depression were significant predictors of the response to MST. Conclusions: We demonstrate that the chronicity, severity, and family history of depression, as well as the presence of melancholic and anxiety symptoms, can serve as clinical predictors of the response to MST. Further research with a larger sample size will be required to verify these preliminary findings.